Consequences of SARS-CoV-2 disease on maternal, perinatal and neonatal outcomes: a retrospective observational cohort study - Sahar H. Abdulghani; Lana A. Shaiba; Mahdya A. Bukhari; Muhab M. Hindi; Shaikh A. Hussain; Adnan A. Hadid (IMR Press, 2021)
Novel coronavirus disease 2019 (COVID-19) continues to affect pregnant women with concerns for adverse maternal and fetal outcomes and is rapidly spreading throughout many countries since it was first reported in China on 31 December 2019. The aim of this study is to describe characteristics, maternal and fetal outcomes among mothers with confirmed maternal SARS-CoV-2 infection. This study presents a retrospective observational cohort study of 62 test-positive cases of coronavirus disease 2019 that presented at an affiliated tertiary university medical city from March 2020 to May 2020. A total of 14 patients (22.5%) presented with obvious typical symptoms of coronavirus disease 2019 associated viremia and were identified after they developed symptoms during admission or after the implementation of universal testing for all obstetric admissions. A total of 62 mothers were screened positive for the SARS-CoV-2 infection. Length of stay was higher in the symptomatic group. The median length of stay was 4 days for the asymptomatic cases while it was 6 days for the symptomatic cases. Amniotic fluid was meconium stained in (12.5%) of the asymptomatic group and in 30.8% in the symptomatic group. Post discharge mothers with asymptomatic SARS-CoV-2 infection were more likely to breastfeed their infants. OR (95% CI) was 1.4 (1.02-1.90) and P-value was 0.0327. There was non-statistically significant absence of perinatal morbidities or mortalities among symptomatic and asymptomatic mothers.